2016
DOI: 10.1891/1058-1243.25.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Content and Presentation of Content in Parental Education Groups in Sweden

Abstract: This study investigated parents' experiences of parental education groups at antenatal and child health care centers, including content, presentation of content, the leader's role, and the importance of other participating parents. Twenty-one interviews with 26 parents from 6 cities across Sweden were analyzed with 3 content analysis approaches. Parents expressed both satisfaction and dissatisfaction with the content, presentation of content, and the leader's role. They reported that social contact with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 20 publications
0
32
0
5
Order By: Relevance
“…The findings might be explained by earlier studies revealing a lack of training in group leadership for leaders (Forslund Frykedal et al, ; Lefèvre et al, ), lack of competence in managing groups and teaching methods, as well as difficulties in identifying parents' needs (Forslund Frykedal et al, ). The results also support and can provide better understanding of parents' reports of a shortage of group activities (Berlin et al, ; Forslund Frykedal & Rosander, ), a lack of leadership ability in PE groups (Berlin et al, ; Forslund Frykedal et al, ), and the most frequent teaching method used in PE groups being lectures (Berlin et al, ). The present study showed that leaders used their expert role most of the time, and mediated information and expert knowledge.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…The findings might be explained by earlier studies revealing a lack of training in group leadership for leaders (Forslund Frykedal et al, ; Lefèvre et al, ), lack of competence in managing groups and teaching methods, as well as difficulties in identifying parents' needs (Forslund Frykedal et al, ). The results also support and can provide better understanding of parents' reports of a shortage of group activities (Berlin et al, ; Forslund Frykedal & Rosander, ), a lack of leadership ability in PE groups (Berlin et al, ; Forslund Frykedal et al, ), and the most frequent teaching method used in PE groups being lectures (Berlin et al, ). The present study showed that leaders used their expert role most of the time, and mediated information and expert knowledge.…”
Section: Discussionmentioning
confidence: 54%
“…Worldwide, expectant and new parents are offered early parenting support in parental education (PE) groups, which is a health‐promoting effort focusing on preparing parents for childbirth and a healthy transition to parenthood (Barlow, Smailgagic, Huband, Roloff, & Bennett, ; Berlin, Törnkvist, & Barimani, ; Bryanton, Beck, & Montelpare, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations